Pengaruh Metode Pembelajaran Kooperatif Tipe Make-A-Match Terhadap Kemampuan Pemahaman Konsep Matematika Siswa SMA Negeri 4 Yogyakarta - Don Bosko, Yohanes; Khuzaini, Nanang (COGNITIVISM: Journal of Educational Research and Development, 2026)
This study investigates the impact of the "Make-a-Match" method on students' mathematical conceptual understanding at SMA Negeri 4 Yogyakarta, while comparing its effectiveness to conventional teaching methods. Employing a quantitative approach, the research followed a quasi-experimental non-equivalent control group design. Data were collected using a specialized test instrument, which was validated by subject matter experts and confirmed through rigorous validity and reliability testing. Analysis was performed using paired and independent sample t-tests at a 5% significance level, with all data satisfying the prerequisites for normality and homogeneity. The research results show that the use of the make-a-match method has a significant positive effect on students' mathematical concept understanding ability, which is evidenced by the change in the average of students' mathematical concept understanding ability from 45.63 to 69.22. Similarly, the conventional method is proven by the increase in the average of students' mathematical concept understanding ability from 38.28 to 52.66. However, the effect of the make-a-match method on students' mathematical concept understanding ability is better compared to the conventional method, which is evidenced by the difference in the posttest averages of the experimental class and the control class, namely 69.22 and 52.66. Therefore, it is concluded that the use of the make-a-match method has a positive effect on the mathematical concept understanding ability of students at SMA Negeri 4 and is better than the conventional method.